STRUKTUR KOMUNITAS MAKROZOOBENTOS DI SUNGAI PAKIL KABUPATEN BANGKA - Desinawati Desinawati; Wahyu Adi; Eva Utami (Department of Aquatic Resources Management, Faculty of Agriculture, Fisheries, and Biology, University of Bangka Belitung, 2018)
Pakil River which is located in Paya Benua Village, West Mendo District, Bangka Regency. This river has an impact from mining activities which then affect the macrozoobenthos community. The purpose of this study was to determine the macrozoobenthic community structure in the Pakil River and determine the effect of water quality on macrozoobenthos in the Pakil River. The study was conducted in April 2018 in the waters of the Pakil River, Paya Benua Village, West Mendo District, Bangka Regency. The macrozoobentos sample was taken purposively at 6 observation stations. The results showed that 4 species of macrozoobenthos. With a diversity index of 0.9195 in the category of low diversity, uniformity index of 0.663 was classified as stable and the dominance index of 0.4425 was in the medium category. The effect of TSS parameters and depth greatly affect the life of the macrozoobenthos, while the ones that have sufficient influence are the parameters of current velocity and DO, then those that have no effect are the parameters of pH, temperature and sand fraction.